Association of Age and BP Variability with Long-term Mortality in Hemodialysis Patients - Ha Yeon Kim; Yong Un Kang; Chang Seong Kim; Joon Seok Choi; Eun Hui Bae; Seong Kwon Ma; Soo Wan Kim (Kidney & Blood Pressure Research, 2014)
Background/Aims: Blood pressure (BP) variability is known as a poor prognostic factor for cardiovascular outcomes. This study assessed the prognostic significance of BP variability in association with increasing age in hemodialysis patients. Methods: We retrospectively analyzed 2,174 patients on hemodialysis from March 2005 to December 2012. The impact of intradialytic and interdialytic BP variability on all-cause mortality according to age groups was analyzed. Results: Kaplan-Meier survival curves for 5-year cumulative mortality showed higher mortality in patients with higher intradialytic systolic and diastolic BP variability as well as interdialytic systolic and diastolic BP variability (log-rank p=0.006, Conclusion: The overall mortality was associated with BP variability in patients aged <55 years, but not in older ages. This result suggests that younger hemodialysis patients with BP variability require further medical attention and intervention to reduce BP variability.